Efficient production method of digital heat transfer paper

By optimizing raw materials and processes, the tensile strength and fold resistance of digital thermal transfer paper are improved, and the problems of low efficiency and unstable performance in traditional production methods are solved, and efficient production and good performance digital thermal transfer paper is achieved.

CN119266018AActive Publication Date: 2025-01-07WU ZHOU TE ZHONG ZHI YE (JIANG XI) YOU XIAN GONG SI

Patent Information

Application Number
CN202411492930.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-07
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The traditional digital thermal transfer paper production methods have problems such as low production efficiency, unstable paper performance, and inconsistent tensile strength and fold resistance.

Method used

By optimizing the selection of raw materials and improving the preparation process of the glue solution and coating glue solution, and combining modified starch, styrene-propylene surface glue, rosin glue, light calcium carbonate, sodium carboxymethylcellulose and other substances, precisely control production Key parameters in the process to improve paper quality and production efficiency.

Benefits of technology

It realizes efficient production of digital thermal transfer paper, improves the tensile strength and fold resistance of the paper, and ensures good printing suitability and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100552040000121
    Figure BDA0005100552040000121
  • Figure BDA0005100552040000122
    Figure BDA0005100552040000122
  • Figure BDA0005100552040000131
    Figure BDA0005100552040000131
Patent Text Reader

Abstract

The invention discloses an efficient production method of digital heat transfer paper, and belongs to the technical field of papermaking. The method comprises the following steps: mixing modified starch and water, and heating to form a sizing solution; a styrene-acrylic surface sizing agent and rosin size are mixed, and light calcium carbonate and sodium carboxymethyl cellulose are mixed, so that a surface sizing solution and a coating glue solution are prepared respectively; pulping, diluting and pulping the pulp to form mixed pulp with proper beating degree; the method comprises the following steps: adding an internal sizing solution and a PPE wet strength agent into a mixed slurry, screening and purifying the slurry through a slushing pump, a sand remover and a pressurized screen, then forming on a net, simultaneously adding auxiliary agents such as polyethyleneimine, calcium silicate and silica sol, and finally obtaining the digital heat transfer printing paper with excellent tensile strength and folding strength after squeezing dehydration, surface sizing and drying of a paper sheet. Compared with the prior art, the method disclosed by the invention not only improves the production efficiency, but also ensures the printing quality and the mechanical property of the digital heat transfer paper, and meets the requirements of the market on high-performance transfer paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of papermaking, and in particular to a method for efficiently producing digital thermal transfer paper. Background Art

[0002] With the rapid development of digital printing technology, the market demand for digital thermal transfer paper as a special printing material is growing. Digital thermal transfer paper can transfer digital images to various substrates such as clothing, ceramics, metals, etc. through thermal transfer technology, and is widely used in personalized customized products. However, the traditional production method of digital thermal transfer paper has some limitations, such as low production efficiency, unstable paper performance, tensile strength and folding resistance not meeting the standards, etc.

[0003] Chinese invention patent CN106758536A discloses a method for producing light-coated digital thermal transfer paper, which includes the steps of preparing sizing solution in pulp, preparing surface sizing solution, preparing surface coating sizing solution, pulp crushing, pulping-mixing process, screen forming, surface sizing, coating and the like. The invention provides a method for producing light-coated digital thermal transfer paper with good ink compatibility, fast drying speed, high transfer rate and no curling. The production method organically combines the production of coating with the production of base paper, and the production is completed in one go. However, the tensile strength and folding endurance of the light-coated digital thermal transfer paper prepared by the invention are poor, which limits its use in certain application scenarios. Summary of the invention

[0004] In view of the defects of the prior art, the present invention aims to provide a high-efficiency production method for digital thermal transfer paper, which improves the quality and production efficiency of paper by optimizing the selection of raw materials, improving the preparation process of sizing solution and coating glue solution, and accurately controlling the key parameters in the production process, while ensuring that the final product has good printability and mechanical properties.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] A method for efficiently producing digital thermal transfer paper is as follows, in parts by weight:

[0007] Step 1, preparation of slurry sizing solution: add 3-5 parts of modified starch to 100-120 parts of water, stir evenly, heat to 90-100° C., keep warm for 10-30 minutes, and prepare slurry sizing solution;

[0008] Step 2, preparation of surface sizing solution: adding 0.5-2 parts of styrene acrylic surface sizing agent and 40-60 parts of rosin glue to 250-350 parts of water, mixing, heating to 90-100° C., stirring evenly, and keeping warm for 10-30 minutes to obtain surface sizing solution;

[0009] Step 3, preparation of coating glue: adding 0.5-2 parts of light calcium carbonate and 3-5 parts of sodium carboxymethyl cellulose to 10-15 parts of water and stirring evenly to obtain coating glue;

[0010] Step 4, pulp crushing and beating: crush the softwood pulp for 10 to 30 minutes, then dilute with water to form a mixed pulp;

[0011] Step 5, slurry preparation: pump the mixed slurry into a batching tank, add 5-10 parts of the sizing solution prepared in step 1 per ton of paper and 15-18 parts of the PPE wet strength agent per ton of pulp into the batching tank and mix them evenly;

[0012] Step 6, forming on the screen: after the slurry in step 5 is prepared to a concentration of 0.7% to 0.9%, it is screened and purified by a slurry pump, a sand remover, and a pressure screen, and then formed on the screen; 0.1 to 0.3 parts of polyethyleneimine per ton of paper and 35 to 45 parts of calcium silicate per ton of paper are added to the inlet of the slurry pump; 2 to 4 parts of silica sol per ton of paper are added to the low-concentration stabilizing box; 5 to 10 parts of GBS-02 papermaking surface sizing agent per ton of paper are added to the outlet pipe of the low-concentration stabilizing box; the paper sheets are obtained by forming on the screen, squeezing, dehydrating, and drying;

[0013] Step 7, sizing and drying: sizing the dried base paper surface, the sizing amount of the surface sizing solution prepared in step 2 is 1-3 g / m 2 , applied to the front of the paper sheet; the amount of the coating glue prepared in step 3 is 1 to 2 g / m 2 , applied on the reverse side of the paper; the coated paper first enters the non-contact hot air drying oven for pre-drying, and then enters the post-drying section for final drying. The moisture content of the paper after final drying is 3-5%;

[0014] Step 8, rewinding and packaging: rewinding, the end surface of the rewinding is neat, the paper surface is flat, and finally packaging is performed to obtain the finished product.

[0015] In step 4, water is added to dilute the slurry to a weight concentration of 3.5-4.5%.

[0016] In step 4, the mixed slurry is beaten to a beating degree of 25 to 27 0 Mixed slurry of SR.

[0017] In step 5, the PPE wet strength agent is obtained by diluting the PPE wet strength agent stock solution by 8 to 12 times with water.

[0018] The pressing section of the squeezing and dehydration in step 6 is composed of four rollers and three pressing zones, and the pressures of the three pressing zones are: 45-55 kN / m 2 , 65~75kN / m 2 , 105~115kN / m 2The dryness of the wet paper after pressing is 40-48%, and the moisture content of the dried paper is 3-5%.

[0019] In step 8, the rewinding speed is controlled at 200-400 m / min, and the basis weight is controlled at 70-90 g / m 2 , the moisture content is controlled at 4-5%.

[0020] The preparation method of the modified starch is as follows, in parts by weight:

[0021] S1. Add 4 to 6 parts of mixed starch into water, adjust the water content to 25 to 35%, and mix them evenly in a high-speed mixer at 70 to 90° C. to obtain gelatinized starch; add 0.5 to 0.7 parts of sorbitol, 0.3 to 0.5 parts of N, N-di(2,3-epoxypropyl)isopropylamine, and 0.005 to 0.02 parts of sodium persulfate into the gelatinized starch, heat and stir to control the temperature at 60 to 80° C., and stir for 1 to 3 hours; add 2 to 5 mol / L of dilute hydrochloric acid dropwise to adjust the pH value to 7 to 8 to obtain a mixture;

[0022] S2, putting the mixed material prepared in step S1 into a twin-screw extruder for extrusion, and setting the screw speed to 200-400rpm; injecting 0.04-0.06 parts of acetone aldehyde into the fifth barrel of the extruder with a liquid spray gun; putting the extruded mixed material into a γ-ray radiation field for radiation irradiation, and the irradiation dose is 6-10kGy, and the irradiation time is 3-5 hours; putting the irradiated mixed material into an oven for drying for 3-8 hours, and the oven temperature is set to 60-80°C; then cooling at room temperature; grinding with a ball mill to pass through a 200-400 mesh sieve to obtain modified starch.

[0023] The mixed starch is a mixture of cassava starch, corn starch and potato starch in equal quantities.

[0024] The temperature gradient of the twin-screw extruder is set to 65-75°C, 85-95°C, 105-115°C, 115-125°C, 125-135°C, 135-145°C.

[0025] In the digital thermal transfer paper efficient production method of the present invention, the functions of each substance are as follows:

[0026] As the main component of the sizing solution in pulp, modified starch enhances the cohesion and sizing effect of paper, and improves the strength and water resistance of paper.

[0027] Styrene acrylic surface sizing agent is mixed with rosin sizing agent for surface sizing to improve the surface strength and printability of paper.

[0028] Rosin glue is mixed with styrene acrylic surface sizing agent and used for surface sizing to increase the water resistance and printing adaptability of paper.

[0029] Light calcium carbonate is used as a filler in coating glue to improve the smoothness and whiteness of paper.

[0030] Sodium carboxymethyl cellulose is used as a binder for coating glue to enhance the adhesion of the coating and the coating properties of paper.

[0031] Coniferous wood pulp is the main raw material for papermaking and provides the basic strength and structure of paper.

[0032] PPE wet strength agent increases the strength of paper in a wet state, improving the toughness and performance of paper.

[0033] Polyethyleneimine acts as a retention aid, helping to increase the retention of fillers and fibers in paper and improve the strength of paper.

[0034] Calcium silicate is used as a filler to improve the smoothness and printability of paper.

[0035] Silica sol is used as an additive to improve the coating properties of paper and increase the strength of paper.

[0036] GBS-02 papermaking surface sizing agent further enhances the surface sizing effect of paper, improves the water resistance and printability of paper.

[0037] Methylglyoxal, as a cross-linking agent, enhances the cross-linking density of modified starch and improves the mechanical strength and folding resistance of paper.

[0038] Sorbitol acts as a plasticizer, increasing the plasticity of starch, making it easier to process and modify.

[0039] N,N-di(2,3-epoxypropyl)isopropylamine is used as a cationic etherifying agent to introduce cationic groups into the starch molecular chain, thereby enhancing its binding force with the fiber.

[0040] Sodium persulfate acts as an initiator to promote the etherification reaction of starch.

[0041] Dilute hydrochloric acid is used to adjust the pH value to ensure the smooth progress of the reaction.

[0042] Gamma-ray radiation fields are used for radiation treatment of modified starches to further improve their properties.

[0043] The combination and interaction of these substances enable the present invention to produce high-quality digital thermal transfer paper with good printability and mechanical properties.

[0044] Compared with the prior art, it has the following beneficial effects:

[0045] 1) The present invention combines the preparation of modified starch with the production process of digital thermal transfer paper to achieve integrated production, reduce the two processing steps of base paper production and coating processing, and thus improve production efficiency.

[0046] 2) The use of the modified starch of the present invention improves the cohesion and sizing effect of paper, and at the same time, by accurately controlling the preparation and application of the sizing solution and the coating glue solution, the surface properties and printability of the paper are improved, so that the final product has better tensile strength and folding resistance. DETAILED DESCRIPTION

[0047] Main sources of substances:

[0048] Styrene acrylic surface sizing agent, model: MX-611, Mingxiang Chemical Technology (Shandong) Group Co., Ltd.

[0049] Rosin glue: Item No.: HY-500665, Shandong Haoyao New Materials Co., Ltd.

[0050] Light calcium carbonate: mesh size: 3000 mesh.

[0051] PPE wet strength agent stock solution: Product number: JR-1001, Tai'an Jiarun Chemical Co., Ltd.

[0052] Polyethylenimine: CAS: 9002-98-6, Product No.: 20240806, Wuhan Jixinyibang Biotechnology Co., Ltd.

[0053] Calcium silicate: mesh size: 2000 mesh.

[0054] Silica sol: Product number: 0450422, Shandong Yousuo Chemical Technology Co., Ltd.

[0055] GBS-02 papermaking surface sizing agent: Product No.: GBS-02, Guangzhou Tongda Chemical Engineering Co., Ltd.

[0056] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0057] The design idea of ​​the present invention is to optimize the production process of digital thermal transfer paper, and improve the quality and production efficiency of paper by accurately controlling the selection and processing steps of raw materials, as well as the preparation of sizing solution and coating glue solution. Specifically, the cohesion and sizing effect of paper are enhanced by using modified starch, the surface properties of paper are improved by combining styrene acrylic surface sizing agent and rosin glue, and sodium carboxymethyl cellulose and light calcium carbonate are used to improve the uniformity of coating glue solution and the printability of paper. At the same time, by finely controlling the processing of slurry, screen forming, pressing dehydration and drying process, it is ensured that the paper reaches the required dryness and moisture content. In addition, the mixed material is irradiated by γ-ray radiation field, and the preparation of modified starch is injected with methylglyoxal as a cross-linking agent during the extrusion process, which further improves the cross-linking density of modified starch and the mechanical strength of paper. Finally, through the rewinding and packaging steps, a finished product with quantitative, moisture and surface flatness that meet the standards is obtained. This design idea aims to improve product performance through technological innovation and meet the needs of efficient production.

[0058] Example 1

[0059] A method for efficiently producing digital thermal transfer paper is as follows:

[0060] Step 1, preparation of slurry sizing solution: add 4 kg of modified starch into 110 kg of water, stir evenly, heat to 95° C., keep warm for 20 minutes, and prepare slurry sizing solution;

[0061] Step 2, preparation of surface sizing solution: add 1 kg of styrene acrylic surface sizing agent and 50 kg of rosin glue into 300 kg of water, mix, heat to 95°C, stir evenly, and keep warm for 20 minutes to obtain surface sizing solution;

[0062] Step 3, preparation of coating glue: add 1 kg of light calcium carbonate and 4 kg of sodium carboxymethyl cellulose into 12 kg of water and stir evenly to obtain coating glue;

[0063] Step 4, pulp crushing and beating: crush the softwood pulp for 20 minutes, then dilute it with water to a pulp with a weight concentration of 4%, and beat it to a pulp with a beating degree of 26. 0 Mixed slurry of SR;

[0064] Step 5, slurry preparation: pump the mixed slurry into a batching tank, add 8 kg of slurry sizing solution prepared in step 1 per ton of paper and 16 kg of PPE wet strength agent per ton of pulp into the batching tank and mix them evenly. The PPE wet strength agent is obtained by diluting the PPE wet strength agent stock solution with 10 times of water;

[0065] Step 6, forming on the screen: after the slurry in step 5 is prepared to a concentration of 0.8%, it is screened and purified by a slurry pump, a sand remover, and a pressure screen, and then formed on the screen; 0.2kg polyethyleneimine and 40kg calcium silicate per ton of paper are added to the inlet of the slurry pump; 3kg silica sol per ton of paper is added to the low-concentration stabilizing box; 8kg GBS-02 papermaking surface sizing agent per ton of paper is added to the outlet pipe of the low-concentration stabilizing box; the paper sheets are formed on the screen, pressed and dehydrated, and dried; the pressing part of the pressing and dehydrating is composed of four rollers and three pressure zones, and the pressures of the three pressure zones are: 50kN / m 2 、70kN / m 2 、110kN / m 2 ; The dryness of the wet paper after pressing is 45%, and the moisture content of the dried paper is 5%;

[0066] Step 7, sizing and drying: Surface sizing is performed on the dried base paper, and the sizing amount of the surface sizing solution prepared in step 2 is 2 g / m 2 , applied to the front of the paper sheet; the amount of the coating glue prepared in step 3 is 1.5g / m 2 , applied on the reverse side of the paper; the coated paper first enters the non-contact hot air drying oven for pre-drying, and then enters the post-drying section for final drying. The moisture content of the paper after final drying is 4%;

[0067] Step 8: Rewinding and packaging: The rewinding speed is controlled at 300m / min and the basis weight is controlled at 80g / m 2 , the moisture is controlled at 4.1%, the end surface of the rewinding is neat, the paper surface is flat, and finally the finished product is packaged.

[0068] The preparation method of the modified starch is as follows:

[0069] S1. Add 5 kg of mixed starch into water, adjust the moisture content to 30%, and mix well in a high-speed mixer at 80° C. to obtain gelatinized starch; add 0.6 kg of sorbitol, 0.4 kg of N,N-di(2,3-epoxypropyl)isopropylamine, and 0.01 kg of sodium persulfate into the gelatinized starch, heat and stir, control the temperature at 70° C., and stir for 1.5 hours; add 4 mol / L of dilute hydrochloric acid dropwise to adjust the pH value to 7 to obtain a mixture;

[0070] S2, putting the mixed material prepared in step S1 into a twin-screw extruder for extrusion, and setting the screw speed to 300 rpm; setting the temperature gradient of the twin-screw extruder to 70°C, 90°C, 110°C, 120°C, 130°C, and 140°C; injecting 0.05 kg of acetone aldehyde into the fifth barrel of the twin-screw extruder with a liquid spray gun; placing the extruded mixed material into a γ-ray radiation field for radiation irradiation, with an irradiation dose of 8 kGy and an irradiation time of 4 hours; placing the irradiated mixed material into an oven for drying for 5 hours, and setting the oven temperature to 70°C; then cooling at room temperature; grinding the mixed material with a ball mill and passing it through a 300-mesh sieve to obtain modified starch.

[0071] The mixed starch is a mixture of cassava starch, corn starch and potato starch in equal quantities.

[0072] Example 2

[0073] A method for efficiently producing digital thermal transfer paper is basically the same as that of Example 1, the only difference being that the preparation method of the modified starch is different.

[0074] The preparation method of the modified starch is as follows:

[0075] S1. Add 5 kg of mixed starch into water, adjust the moisture content to 30%, and mix evenly in a high-speed mixer at 80° C. to obtain gelatinized starch; add 0.6 kg of sorbitol, 0.4 kg of bis(2-methylpropyl)[(oxirane-2-yl)methyl]amine, and 0.01 kg of sodium persulfate into the gelatinized starch, heat and stir, control the temperature at 70° C., and stir for 1.5 hours; add 4 mol / L of dilute hydrochloric acid dropwise to adjust the pH value to 7 to obtain a mixture;

[0076] S2, putting the mixed material prepared in step S1 into a twin-screw extruder for extrusion, and setting the screw speed to 300 rpm; setting the temperature gradient of the twin-screw extruder to 70°C, 90°C, 110°C, 120°C, 130°C, and 140°C; injecting 0.05 kg of acetone aldehyde into the fifth barrel of the twin-screw extruder with a liquid spray gun; placing the extruded mixed material into a γ-ray radiation field for radiation irradiation, with an irradiation dose of 8 kGy and an irradiation time of 4 hours; placing the irradiated mixed material into an oven for drying for 5 hours, and setting the oven temperature to 70°C; then cooling at room temperature; grinding the mixed material with a ball mill and passing it through a 300-mesh sieve to obtain modified starch.

[0077] The mixed starch is the same as that in Example 1.

[0078] Example 3

[0079] A method for efficiently producing digital thermal transfer paper is basically the same as that of Example 1, the only difference being that the preparation method of the modified starch is different.

[0080] The preparation method of the modified starch is as follows:

[0081] S1. Add 5 kg of mixed starch into water, adjust the moisture content to 30%, and mix well in a high-speed mixer at 80° C. to obtain gelatinized starch; add 0.6 kg of sorbitol, 0.4 kg of (2,3-epoxypropyl) [2- (isobutylene oxy) ethyl] dimethyl ammonium chloride, and 0.01 kg of sodium persulfate into the gelatinized starch, heat and stir, control the temperature at 70° C., and stir for 1.5 hours; add 4 mol / L of dilute hydrochloric acid dropwise to adjust the pH value to 7 to obtain a mixture;

[0082] S2, putting the mixed material prepared in step S1 into a twin-screw extruder for extrusion, and setting the screw speed to 300 rpm; setting the temperature gradient of the twin-screw extruder to 70°C, 90°C, 110°C, 120°C, 130°C, and 140°C; injecting 0.05 kg of acetone aldehyde into the fifth barrel of the twin-screw extruder with a liquid spray gun; placing the extruded mixed material into a γ-ray radiation field for radiation irradiation, with an irradiation dose of 8 kGy and an irradiation time of 4 hours; placing the irradiated mixed material into an oven for drying for 5 hours, and setting the oven temperature to 70°C; then cooling at room temperature; grinding the mixed material with a ball mill and passing it through a 300-mesh sieve to obtain modified starch.

[0083] The mixed starch is the same as that in Example 1.

[0084] Example 4

[0085] A method for efficiently producing digital thermal transfer paper is basically the same as that of Example 1, the only difference being that the preparation method of the modified starch is different.

[0086] The preparation method of the modified starch is as follows:

[0087] S1. Add 5 kg of mixed starch into water, adjust the moisture content to 30%, and mix evenly in a high-speed mixer at 80° C. to obtain gelatinized starch; add 0.6 kg of sorbitol, 0.4 kg of 2,3-epoxypropyltrimethylammonium chloride, and 0.01 kg of sodium persulfate into the gelatinized starch, heat and stir, control the temperature at 70° C., and stir for 1.5 hours; add 4 mol / L of dilute hydrochloric acid dropwise to adjust the pH value to 7 to obtain a mixture;

[0088] S2, putting the mixed material prepared in step S1 into a twin-screw extruder for extrusion, and setting the screw speed to 300 rpm; setting the temperature gradient of the twin-screw extruder to 70°C, 90°C, 110°C, 120°C, 130°C, and 140°C; injecting 0.05 kg of acetone aldehyde into the fifth barrel of the twin-screw extruder with a liquid spray gun; placing the extruded mixed material into a γ-ray radiation field for radiation irradiation, with an irradiation dose of 8 kGy and an irradiation time of 4 hours; placing the irradiated mixed material into an oven for drying for 5 hours, and setting the oven temperature to 70°C; then cooling at room temperature; grinding the mixed material with a ball mill and passing it through a 300-mesh sieve to obtain modified starch.

[0089] The mixed starch is the same as that in Example 1.

[0090] Example 5

[0091] A method for efficiently producing digital thermal transfer paper is basically the same as that of Example 1, the only difference being that the preparation method of the modified starch is different.

[0092] The preparation method of the modified starch is as follows:

[0093] S1. Add 5 kg of mixed starch into water, adjust the moisture content to 30%, and mix well in a high-speed mixer at 80° C. to obtain gelatinized starch; add 0.6 kg of sorbitol, 0.4 kg of N,N-di(2,3-epoxypropyl)isopropylamine, and 0.01 kg of sodium persulfate into the gelatinized starch, heat and stir, control the temperature at 70° C., and stir for 1.5 hours; add 4 mol / L of dilute hydrochloric acid dropwise to adjust the pH value to 7 to obtain a mixture;

[0094] S2. Put the mixed material prepared in step S1 into a twin-screw extruder for extrusion, and set the screw speed to 300 rpm; set the temperature gradient of the twin-screw extruder to 70°C, 90°C, 110°C, 120°C, 130°C, and 140°C; inject 0.05 kg of sodium hexametaphosphate into the fifth barrel of the twin-screw extruder with a liquid spray gun; put the extruded mixed material into a γ-ray radiation field for radiation irradiation, with an irradiation dose of 8 kGy and an irradiation time of 4 hours; put the irradiated mixed material into an oven for drying for 5 hours, and set the oven temperature to 70°C; then cool it at room temperature; use a ball mill to grind it through a 300-mesh sieve to obtain modified starch.

[0095] The mixed starch is the same as that in Example 1.

[0096] Example 6

[0097] A method for efficiently producing digital thermal transfer paper is basically the same as that of Example 1, the only difference being that the preparation method of the modified starch is different.

[0098] The preparation method of the modified starch is as follows:

[0099] S1. Add 5 kg of mixed starch into water, adjust the moisture content to 30%, and mix well in a high-speed mixer at 80° C. to obtain gelatinized starch; add 0.6 kg of sorbitol, 0.4 kg of N,N-di(2,3-epoxypropyl)isopropylamine, and 0.01 kg of sodium persulfate into the gelatinized starch, heat and stir, control the temperature at 70° C., and stir for 1.5 hours; add 4 mol / L of dilute hydrochloric acid dropwise to adjust the pH value to 7 to obtain a mixture;

[0100] S2, putting the mixed material prepared in step S1 into a twin-screw extruder for extrusion, and setting the screw speed to 300rpm; setting the temperature gradient of the twin-screw extruder to 70°C, 90°C, 110°C, 120°C, 130°C, and 140°C; injecting 0.05kg of glyoxal into the fifth barrel of the twin-screw extruder with a liquid spray gun; placing the extruded mixed material into a γ-ray radiation field for radiation irradiation, with an irradiation dose of 8kGy and an irradiation time of 4 hours; placing the irradiated mixed material into an oven for drying for 5 hours, and setting the oven temperature to 70°C; then cooling at room temperature; grinding the mixed material with a ball mill and passing it through a 300-mesh sieve to obtain modified starch.

[0101] The mixed starch is the same as that in Example 1.

[0102] Comparative Example 1

[0103] A method for efficiently producing digital thermal transfer paper is as follows:

[0104] Step 1, preparation of slurry sizing solution: add 4 kg of mixed starch into 110 kg of water, stir evenly, heat to 95°C, keep warm for 20 minutes, and prepare slurry sizing solution;

[0105] Step 2, preparation of surface sizing solution: add 1 kg of styrene acrylic surface sizing agent and 50 kg of rosin glue into 300 kg of water, mix, heat to 95°C, stir evenly, and keep warm for 20 minutes to obtain surface sizing solution;

[0106] Step 3, preparation of coating glue: add 1 kg of light calcium carbonate and 4 kg of sodium carboxymethyl cellulose into 12 kg of water and stir evenly to obtain coating glue;

[0107] Step 4, pulp crushing and beating: crush the softwood pulp for 20 minutes, then dilute it with water to a pulp with a weight concentration of 4%, and beat it to a pulp with a beating degree of 26. 0 Mixed slurry of SR;

[0108] Step 5, slurry preparation: pump the mixed slurry into a batching tank, add 8 kg of slurry sizing solution prepared in step 1 per ton of paper and 16 kg of PPE wet strength agent per ton of pulp into the batching tank and mix them evenly. The PPE wet strength agent is obtained by diluting the PPE wet strength agent stock solution with 10 times of water;

[0109] Step 6, forming on the screen: after the slurry in step 5 is prepared to a concentration of 0.8%, it is screened and purified by a slurry pump, a sand remover, and a pressure screen, and then formed on the screen; 0.2kg polyethyleneimine and 40kg calcium silicate per ton of paper are added to the inlet of the slurry pump; 3kg silica sol per ton of paper is added to the low-concentration stabilizing box; 8kg GBS-02 papermaking surface sizing agent per ton of paper is added to the outlet pipe of the low-concentration stabilizing box; the paper sheets are formed on the screen, pressed and dehydrated, and dried; the pressing part of the pressing and dehydrating is composed of four rollers and three pressure zones, and the pressures of the three pressure zones are: 50kN / m 2 、70kN / m 2 、110kN / m 2 ; The dryness of the wet paper after pressing is 45%, and the moisture content of the dried paper is 5%;

[0110] Step 7, sizing and drying: Surface sizing is performed on the dried base paper, and the sizing amount of the surface sizing solution prepared in step 2 is 2 g / m 2 , applied to the front of the paper sheet; the amount of the coating glue prepared in step 3 is 1.5g / m 2 , applied on the reverse side of the paper; the coated paper first enters the non-contact hot air drying oven for pre-drying, and then enters the post-drying section for final drying. The moisture content of the paper after final drying is 4%;

[0111] Step 8: Rewinding and packaging: The rewinding speed is controlled at 300m / min and the basis weight is controlled at 80g / m 2 , the moisture is controlled at 4.1%, the end surface of the rewinding is neat, the paper surface is flat, and finally the finished product is packaged.

[0112] The mixed starch is a mixture of cassava starch, corn starch and potato starch in equal quantities.

[0113] Test Example 1

[0114] The tensile strength (KN / m) is tested in accordance with GB / T 12914-2018 "Determination of tensile strength of paper and paperboard - Constant rate tensile method (20 mm / min)".

[0115] The test results are shown in Table 1.

[0116] Table 1

[0117]

[0118] Test Example 2

[0119] Folding resistance: The test was conducted using a paper folding resistance tester (Jinan Sanquan Zhongshi Experimental Instrument Co., Ltd., China). Test parameters: At room temperature, paper cut into 5cm×1cm pieces was folded back and forth until the paper broke.

[0120] The test results are shown in Table 2.

[0121] Table 2

[0122]

[0123]

[0124] It can be seen from the data in Table 1 and Table 2 that the digital thermal transfer paper prepared in Example 1 has good tensile strength and folding resistance.

[0125] As a cationic etherifying agent, N, N-di(2,3-epoxypropyl)isopropylamine plays a key role in the preparation process of modified starch. The molecular structure of this compound contains two epoxy groups, which can react with the hydroxyl groups in the starch molecules to form a stable ether bond. This reaction not only improves the cationic properties of starch, but also enhances its adhesion and dispersibility in the paper sizing process. The mechanism of action of N, N-di(2,3-epoxypropyl)isopropylamine is mainly to introduce cationic groups through the ring-opening reaction between its epoxy groups and the hydroxyl groups of starch molecules, thereby obtaining modified starch. The presence of isopropylamine groups in its molecular structure makes the compound have good hydrophilicity and reactivity, and can form a strong cross-linked network between starch molecules, thereby improving the mechanical stability and water resistance of starch. In contrast, the cross-linking agents used in other embodiments may not provide the same degree of cross-linking effect due to different molecular structures, resulting in differences in the performance of the final product.

[0126] In Example 1, methylglyoxal, with a chemical formula of C3H4O2, contains a methyl group, a carbonyl group and an aldehyde group, wherein the carbonyl group is connected to the methyl group. In the paper modification process, the active aldehyde group of methylglyoxal can react with the hydroxyl group in the cellulose molecule by nucleophilic addition to form a Schiff base, thereby enhancing the cross-linking between molecules through polymerization reaction, thereby improving the tensile strength and folding resistance of the paper. The presence of the methyl group of methylglyoxal provides hydrophobicity, which helps to form a stable cross-linked network on the cellulose fiber, thereby improving the mechanical properties of the paper. In contrast, sodium hexametaphosphate is usually used as a chelating agent and pH regulator. Although it can also be used as a cross-linking agent, its cross-linking ability and reactivity may not be as active and effective as organic cross-linking agents. Although glyoxal also has two aldehyde groups, its molecule is smaller and does not contain hydrophobic groups, and may not provide multi-point cross-linking and stability like methylglyoxal. Therefore, in paper modification, methylglyoxal exhibits more excellent performance due to its unique molecular structure and reaction characteristics.

Claims

1. A method for efficiently producing digital thermal transfer paper, characterized in that: The method is as follows, in parts by weight: Step 1, preparation of slurry sizing solution: add 3-5 parts of modified starch to 100-120 parts of water, stir evenly, heat to 90-100° C., keep warm for 10-30 minutes, and prepare slurry sizing solution; Step 2, preparation of surface sizing solution: adding 0.5-2 parts of styrene acrylic surface sizing agent and 40-60 parts of rosin glue to 250-350 parts of water, mixing, heating to 90-100° C., stirring evenly, and keeping warm for 10-30 minutes to obtain surface sizing solution; Step 3, preparation of coating glue: adding 0.5-2 parts of light calcium carbonate and 3-5 parts of sodium carboxymethyl cellulose to 10-15 parts of water and stirring evenly to obtain coating glue; Step 4, pulp crushing and beating: crush the softwood pulp for 10 to 30 minutes, then dilute with water to form a mixed pulp; Step 5, slurry preparation: pump the mixed slurry into a batching tank, add 5-10 parts of the sizing solution prepared in step 1 per ton of paper and 15-18 parts of the PPE wet strength agent per ton of pulp into the batching tank and mix them evenly; Step 6, forming on the screen: after the slurry in step 5 is prepared to a concentration of 0.7% to 0.9%, it is screened and purified by a slurry pump, a sand remover, and a pressure screen, and then formed on the screen; 0.1 to 0.3 parts of polyethyleneimine per ton of paper and 35 to 45 parts of calcium silicate per ton of paper are added to the inlet of the slurry pump; 2 to 4 parts of silica sol per ton of paper are added to the low-concentration stabilizing box; 5 to 10 parts of GBS-02 papermaking surface sizing agent per ton of paper are added to the outlet pipe of the low-concentration stabilizing box; the paper sheets are obtained by forming on the screen, squeezing, dehydrating, and drying; Step 7, sizing and drying: sizing the dried base paper surface, the sizing amount of the surface sizing solution prepared in step 2 is 1-3 g / m 2 , applied to the front of the paper sheet; the amount of the coating glue prepared in step 3 is 1 to 2 g / m 2 , applied on the reverse side of the paper; the coated paper first enters the non-contact hot air drying oven for pre-drying, and then enters the post-drying section for final drying. The moisture content of the paper after final drying is 3-5%; Step 8, rewinding and packaging: rewinding, the end surface of the rewinding is neat, the paper surface is flat, and finally packaging is performed to obtain the finished product.

2. The high-efficiency production method of digital thermal transfer paper according to claim 1, characterized in that: In step 4, water is added to dilute the slurry to a weight concentration of 3.5-4.5%.

3. The high-efficiency production method of digital thermal transfer paper according to claim 1, characterized in that: In step 4, the mixed slurry is beaten to a beating degree of 25 to 27 0 Mixed slurry of SR.

4. The high-efficiency production method of digital thermal transfer paper according to claim 1, characterized in that: In step 5, the PPE wet strength agent is obtained by diluting the PPE wet strength agent stock solution by 8 to 12 times with water.

5. The high-efficiency production method of digital thermal transfer paper according to claim 1, characterized in that: The pressing section of the squeezing and dehydration in step 6 is composed of four rollers and three pressing zones, and the pressures of the three pressing zones are: 45-55 kN / m 2 , 65~75kN / m 2 , 105~115kN / m 2 The dryness of the wet paper after pressing is 40-48%, and the moisture content of the dried paper is 3-5%.

6. The high-efficiency production method of digital thermal transfer paper according to claim 1, characterized in that: In step 8, the rewinding speed is controlled at 200-400 m / min, and the basis weight is controlled at 70-90 g / m 2 , the moisture content is controlled at 4-5%.

7. The high-efficiency production method of digital thermal transfer paper according to claim 1, characterized in that: The preparation method of the modified starch is as follows, in parts by weight: S1. Add 4 to 6 parts of mixed starch into water, adjust the water content to 25 to 35%, and mix them evenly in a high-speed mixer at 70 to 90° C. to obtain gelatinized starch; add 0.5 to 0.7 parts of sorbitol, 0.3 to 0.5 parts of N, N-di(2,3-epoxypropyl)isopropylamine, and 0.005 to 0.02 parts of sodium persulfate into the gelatinized starch, heat and stir to control the temperature at 60 to 80° C., and stir for 1 to 3 hours; add 2 to 5 mol / L of dilute hydrochloric acid dropwise to adjust the pH value to 7 to 8 to obtain a mixture; S2, putting the mixed material prepared in step S1 into a twin-screw extruder for extrusion, and setting the screw speed to 200-400rpm; injecting 0.04-0.06 parts of acetone aldehyde into the fifth barrel of the extruder with a liquid spray gun; putting the extruded mixed material into a γ-ray radiation field for radiation irradiation, and the irradiation dose is 6-10kGy, and the irradiation time is 3-5 hours; putting the irradiated mixed material into an oven for drying for 3-8 hours, and the oven temperature is set to 60-80°C; then cooling at room temperature; grinding with a ball mill to pass through a 200-400 mesh sieve to obtain modified starch.

8. The high-efficiency production method of digital thermal transfer paper according to claim 7, characterized in that: The mixed starch is a mixture of cassava starch, corn starch and potato starch in equal quantities.

9. The high-efficiency production method of digital thermal transfer paper according to claim 7, characterized in that: The temperature gradient of the twin-screw extruder is set to 65-75°C, 85-95°C, 105-115°C, 115-125°C, 125-135°C, 135-145°C.

10. A digital thermal transfer paper, characterized in that: Prepared by the production method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Production method of high stiffness heat transfer raw paper

    CN103726396A

  • Method for producing light coating digital heat transfer paper

    CN106758536A

  • Heat sublimation digital transfer paper and production method

    CN107435275A

  • Preparation method of cationic starch

    CN110194806A

  • Thermal dye sublimation transfer paper and production process thereof

    CN114737413A

Cited By

  • Preparation method of papermaking sizing starch

    CN119842840A